Piptide Chemotypes for Perturbation of the Interaction of Urokinase with Its Receptor - Arancillo, Maritess; Lin, Chen-Ming; Burgess, Kevin (Journal of medicinal chemistry, 2022)
Only a few small molecules that disrupt the uPA and uPA receptor (uPAR) interaction have been discovered despite decades of research in the area, and none have been approved in clinical trials. Research reported here features two new ways of considering the problem of discovering small molecules to disrupt uPA•uPAR, specifically in terms of chemotype design and method of evaluation. Chemotypes used in this work are piptides ( Arancillo . Angew. Chem., Int. Ed., 2021, 60, 6653−6659 ) with side chains corresponding to the uPA loop that binds uPAR. Further, hybrids of 1 and another uPAR ligand developed in these labs (2), i.e., 3 and 4, were also designed and tested. All the piptide chemotypes bound uPAR at concentrations of 50 μM or less. Members of this series had K i values <3 μM and showed favorable responses in cellular assays; these data are comparable with the best small molecule uPA•uPAR disruptors in the literature (from conventional screening).